Kualitas Birokrasi Pelayanan Publik Dalam Penyelenggaraan Pemerintahan Di Era Otonomi Daerah (Studi Kasus di Kabupaten Tulang Bawang, Lampung) - Akhmad Suharyo (PUBLICA, 2011)
This research is a qualitative one. Direct observation are held in the Department of Civil Population and Family Planning, and Integrated One-step Service office. During the research process a range of primary and secondary data was collected. The primary data came via some interviews with the recepients of public services and questionaires that are distributed to them, while secondary data source included the legal products from the central government and local government. The result showed that: 1) the quality of public service bureaucracy in Tulang Bawang District in the era of regional autonomy has not fulfilled the target that was expected by service users, 2) the factors that affect the quality of public service bureaucracy are the large bureaucratioal structure, the unprofessional behavior of the bureaucracy, the incompetence bureaucratic leadership behavior, while ethics has not yet become priority in delivering public services, 3) some efforts that can be done in order to improve the quality of public services are: (a) enhancing the functions of local government institutions, including compose better system and procedures, restructure the organization and its working procedures, and evaluate services, (b) improving the quality of personnel resources, including increase their competences, gift, reward and punishment, (c) improving service performance, including the ethics of services, discipline of services, transparency of costs, better handling public complaints, use of information technology, (d) enhancing the function of supervision through the performance of service personnel, including internal and external controls.